IMPROVING STUDENTS’ VOCABULARY MASTERY THROUGH APHORISMS (Web of Teachers: Inderscience Research, 2024)
The learning of vocabulary is an important part in foreign language learning. Vocabulary is considered as central in language teaching and is of paramount importance to a language learner. Improving vocabulary skill among English language learners is a challenge faced by many teachers. The objective of the article is to find out the way in improving students’ vocabulary skill through aphorisms.